2015
DOI: 10.1111/mec.13245
|View full text |Cite|
|
Sign up to set email alerts
|

RAD genotyping reveals fine‐scale genetic structuring and provides powerful population assignment in a widely distributed marine species, the American lobster (Homarus americanus)

Abstract: Deciphering genetic structure and inferring connectivity in marine species have been challenging due to weak genetic differentiation and limited resolution offered by traditional genotypic methods. The main goal of this study was to assess how a population genomics framework could help delineate the genetic structure of the American lobster (Homarus americanus) throughout much of the species' range and increase the assignment success of individuals to their location of origin. We genotyped 10 156 filtered SNPs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

33
252
4
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 253 publications
(291 citation statements)
references
References 108 publications
(206 reference statements)
33
252
4
2
Order By: Relevance
“…Broader phylogeographic patterns of subdivision between the Gulf of Maine, eastern Nova Scotia, and the GSL are generally consistent with previous studies of intertidal (Dillon and Manzi 1992;Kelly et al 2006;Baker et al 2008) and subtidal species (Kenchington et al 2006;St-Onge et al 2013;Benestan et al 2015). Although the AMOVA results indicated strong regional differentiation for both species, levels of intraspecific genetic variation differed substantially between the species.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Broader phylogeographic patterns of subdivision between the Gulf of Maine, eastern Nova Scotia, and the GSL are generally consistent with previous studies of intertidal (Dillon and Manzi 1992;Kelly et al 2006;Baker et al 2008) and subtidal species (Kenchington et al 2006;St-Onge et al 2013;Benestan et al 2015). Although the AMOVA results indicated strong regional differentiation for both species, levels of intraspecific genetic variation differed substantially between the species.…”
Section: Discussionsupporting
confidence: 88%
“…In addition, samples of C. volutator from DGB clustered with samples from the Gulf of Maine (Einfeldt and Addison 2013), but in our collections from DGB, T. obsoleta was genetically identical to the Bay of Fundy, whereas M. petalum was genetically more similar to samples from eastern Nova Scotia. Population genetic studies in other species also show mixed patterns across this transition zone (e.g., Gartner-Kepkay et al 1980;Dillon and Manzi 1992;Addison and Hart 2004;Evans et al 2004;Kelly et al 2006;Kenchington et al 2006;Jennings et al 2009;So et al 2011;Owen and Rawson 2013;St-Onge et al 2013;Benestan et al 2015;Govindarajan et al 2015), but as these studies only sampled one population in or at the mouth of the bay, they provide little resolution to the boundaries of phylogeographic transition. Although many species of marine invertebrates sampled in the Bay of Fundy appear isolated from populations studied elsewhere, incongruence in the location of the break suggests that the physical boundaries to gene flow across the gyre depend on a variety of factors including both dispersal ability and evolutionary history.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, genomewide divergence was so prominent that background genomic variation (i.e., neutral SNPs) explained an order of magnitude more of the variation between northern and southern groups than observed in native species in the region (e.g., sea scallop, Van Wyngaarden et al., 2017), and locus‐specific F ST values were an order of magnitude larger across the genome than observed in native species [e.g., American lobster, Homarus americanus , Benestan et al. (2015) or sea scallop]. This work builds directly on previous studies describing the spatial variation of these two invasions by providing enhanced genomic and geographic resolution of the differences.…”
Section: Discussionmentioning
confidence: 83%
“…More recent ex panded coverage suggests significantly greater genetic structure (Benestan et al 2015) in Atlantic Canada than previously reported. Given the high abundance of lobsters in some environments and large dispersal potential (e.g.…”
Section: Biogeographic Variationmentioning
confidence: 58%